The Effect of High-intensity Interval Training and L-carnitine on the Expression of Genes Involved in Lipid and Glucose Metabolism in the Liver of Wistar Rats - Shahouzehi,Beydolah (2023)
Abstract Metabolic flexibility is the capacity of a system to adjust fuel (primarily glucose and fatty acids) oxidation based on nutrient availability. Pyruvate Dehydrogenase Kinase 4 (PDK4) is one of the main enzymes that plays a critical role in metabolic flexibility. In the current study, we examined the expression of genes involved in metabolism in the liver of male rats. Thirty-two male Wistar rats (8 week old) were randomly divided into 4 groups (n = 8); 1. Control, 2. Training (do HIIT training for 4 weeks), 3. LCAR (received 200 mg / kg of L-carnitine, daily), 4. Training + L-carnitine (LCAR-HIIT). The gene expression was measured by Real-time PCR and quantified by 2-∆∆Ct method. Sterol regulatory element-binding protein-1c (SREBP-1c) expression was significantly higher in the LCAR (p = 0.018) and HIIT (p = 0.001) group than in the LCAR- HIIT group. Stearoyl-Coenzyme A desaturase-1 (SCD1) expression in HIIT (p = 0.007, p < 0.001) and LCAR-HIIT (p < 0.001, p = 0.003) groups was significantly increased and decreased compared to the control group and LCAR group, respectively. PDK4 expression was significantly reduced by combination of LCAR-HIIT compared to the control group. In sum, the administration of carnitine and HIIT is very useful and can conduct this by reducing the expression of lipogenic genes such as SREBP-1c and SCD1 as well as increasing the expression of Carnitine palmitoyltransferase 1 (CPT1).